2017
DOI: 10.1007/s00330-017-5183-3
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion MR imaging of early cervical carcinoma: correlation between imaging parameters and tumor-stroma ratio

Abstract: • TSR is a recognized independent prognostic factor in many solid tumours. • D and f values measured by IVIM MRI are independently correlated with TSR while D* is not. • IVIM offers the potential to predict TSR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 37 publications
1
30
1
Order By: Relevance
“…This study assessed HIF‐1α expression by using the IVIM technique, and showed that, among all the IVIM parameters, D had the highest performance of assessing HIF‐1α expression. A possible explanation is that D reflects the slow component of diffusion, and is related to cell density, histologic grade, and the tumor stroma ratio, which is closely correlated with tumor hypoxia . In addition, this study showed that the f value had a lower correlation with HIF‐1α expression.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…This study assessed HIF‐1α expression by using the IVIM technique, and showed that, among all the IVIM parameters, D had the highest performance of assessing HIF‐1α expression. A possible explanation is that D reflects the slow component of diffusion, and is related to cell density, histologic grade, and the tumor stroma ratio, which is closely correlated with tumor hypoxia . In addition, this study showed that the f value had a lower correlation with HIF‐1α expression.…”
Section: Discussioncontrasting
confidence: 57%
“…However, this study found that there was no correlation between the D* value and HIF‐1α expression. A possible explanation is that D* has some technical limitations such as its huge standard deviation, data instability, and its dependence on SNR, and thus D* is very difficult to model and measure accurately, which may be the main reason why D* is not useful in predicting the hypoxia status …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations